BUDIDAYA HIDROPONIK UNTUK TERAPI OKUPASI DAN PEMBERDAYAAN ORANG DENGAN GANGGUAN JIWA - Lavita Permata Arni Sari; Wulandari Ratnasari; Duvan Awang Prayoga; Yoga Prasetya; Nindy Puspitasari; Verania Cahyadewi; Ah. Sofi (UPT. PKM UB, 2024)
This study aims to describe the implementation and advantages and disadvantages of hydroponic cultivation for occupational therapy for people with mental disorders. The Sambibulu Village Government has provided a place to facilitate the recovery of people with mental disorders through an integrated mental health service post or called mental health posyandu. Apart from focusing on healing, Sambibulu Village's mental health posyandu activities also provide training to people with mental disorders. The approach used is a personal approach through interviews, dialogue and observation, with the socialization method. The results of the study show that the implementation of hydroponic cultivation targeting ODGJ at Posyandu Jiwa, Sambibulu Village, Taman District, Sidoarjo Regency, takes the form of occupational therapy with a series of planning activity processes, making observations and preparing equipment, the implementation includes sowing seeds, as well as evaluating care until harvest time. Hydroponic cultivation activities have the advantage of providing occupational therapy for people with mental disorders, while the disadvantages include that the initial investment is quite large, which can be an obstacle if funds are limited and requires certain technical knowledge and skills in regulating pH and mixing nutrients.